Consequences of a double hit of stress during the perinatal period and midlife in female rats: Mismatch or cumulative effect?. (July 2018) - Van Camp, Gilles; Cigalotti, Jenny; Bouwalerh, Hammou; Mairesse, Jérôme; Gatta, Eleonora; Palanza, Paola; Maccari, Stefania; Morley-Fletcher, Sara
Highlights: Females animal models deserve to be more investigated. Programming of stress-related diseases can be reversed by adult stress. The mechanism is a more dynamic phenotype in early life stressed individuals. The interplay between experiences during early life and adulthood is non-additive. Abstract: The interplay between experiences during critical developmental periods and later adult life is crucial in shaping individual variability in stress coping strategies. Exposure to stressful events in early life has strongly programs an individual's phenotype and adaptive capabilities. Until now, studies on programming and reversal strategies in early life stress animal models have been essentially limited to males. By using the perinatal stress (PRS) rat model (a model more sensitive to aging changes) in middle-aged females, we investigated the behavioral and endocrine responses following exposure in later life to an unpredictable chronic mild stress (uCMS) condition for six weeks. PRS by itself accelerated the ageing-related-disruption in the estrous cycle and led to reductions in the levels of estradiol. It also reduced motivational and risk-taking behavior in later life, with PRS females being characterized by a reduction in self-grooming in the splash test, in the exploration of the light compartment in the light/dark box test and in the time spent eating a palatable food in the novelty-induced suppression feeding test. PRS females showed impaired regulation of plasma glucose and insulin levels following a glucose challenge, with a hyperglycemic phenotype, and disrupted feedback of the HPA axis after acute stress with respect to controls. Remarkably, all PRS-induced alterations were modified by exposure to the uCMS procedure, thus resulting in a disease-dependent intervention; controls were not affected by uCMS, except for a slight and transient reduction in body weight, while PRS females displayed a reduced body weight gain for the entire duration of the uCMS procedure. Interestingly, the effects of uCMS on PRS females were still observed up to two months after its termination and the females displayed heightened rhythms of locomotor activity and enhanced sensitivity to reward with respect to controls exposed to uCMS. Our findings indicate that many parameters of the PRS female adult phenotype are shaped by both early and later life experiences in a non-additive way. As a consequence, early stressed individuals may be programmed with a more dynamic phenotype than non-stressed individuals.